Modes of the Reactive Power Source Controlled by the Phase-Shifting Transformer - Golub I.V.; Zaitsev D.A.; Tirsu M.S. (Problems of the Regional Energetics)
The purpose of this work is to develop a diagram version of the compensating device, and its control strategies using a phase-shifting transformer device. The purpose has been achieved performing a complex of research based on structural-simulation models both for the compensating device as a whole, and for the phase-shifting transformer. Based on the phase-shifting transformer model, calculation experiments in idle, short-circuit and under load conditions have been carried out. The obtained data allowed to determine the energy characteristics of the object of research and to perform analysis of its characteristics during the process of adjusting the angle of phase shift. The paper also provides the results of research in the regime's parameters issue of the device as a whole. The obtained data confirmed the functionality of the proposed reactive power source. The novelty of the work consists in the development of innovative circuit variant of controlled compensating device. Its component parts are susceptances, allowing carrying out a symmetrical adjustment of reactive power both consumed and offered to the network in a predetermined range. A control diagram for adjusting windings of a phase-shifting transformer has been proposed. The control's principle of power electronic keys provides control of the phase shift of the voltage at the output terminals of the device in the range from 0° to 60° at 15 switching positions. The proposed technical solution provides symmetrical smooth control of reactive power in a wide range at the point of connection of the device to the network.